Question
Asked Sep 29, 2019
107 views

If f(x)=x+4 and g(x)=x−4,

 

(a) f(g(x))=  
(b) g(f(x))=  
(c) Thus g(x) is called an

check_circle

Expert Answer

Step 1

Given,

help_outline

Image Transcriptionclose

f(x)x+4 and g(x)=x-4

fullscreen
Step 2

a). 

help_outline

Image Transcriptionclose

f(g(x)) f(x-4) replacing x by x-4 in f (x)] =(x-4)+4 =x

fullscreen
Step 3

b). ...

help_outline

Image Transcriptionclose

g(f(x)) g(x+4) replacing x by x+4 in g(x)] = (x+4)-4 = x

fullscreen

Want to see the full answer?

See Solution

Check out a sample Q&A here.

Want to see this answer and more?

Solutions are written by subject experts who are available 24/7. Questions are typically answered within 1 hour.*

See Solution
*Response times may vary by subject and question.
Tagged in

Math

Calculus

Functions